Antifungals in severe asthma. Issue 1 (January 2015) - Parulekar, Amit D.; Diamant, Zuzana; Hanania, Nicola A.
Abstract : Purpose of review: Despite guideline-based treatment, many patients with severe asthma continue to have uncontrolled disease. Fungal allergy is being increasingly recognized in the pathogenesis of severe asthma. Limited data exist on the approach to treatment of fungal asthma. This review summarizes existing evidence on the use of antifungal agents in allergic bronchopulmonary aspergillosis (ABPA) and severe asthma with fungal sensitization (SAFS), and highlights needed areas of future investigation. Recent findings: Recent studies evaluating oral triazole therapy in ABPA appear to support triazole use in a carefully considered clinical setting, whereas studies assessing triazole use in SAFS have yielded mixed results. Despite early encouraging findings that oral triazole use may improve asthma symptoms, stabilize lung function, decrease inhaled and systemic corticosteroid requirements, and alter serum biomarkers, overall data are limited. Appropriate patient selection, as well as choice of the optimal drug, dose, frequency, and duration of therapy, remains poorly defined. Summary: The role of antifungal therapy in severe asthma remains unclear. Early studies have suggested a possible benefit of some antifungal agents, such as oral triazoles in ABPA and SAFS; however, routine clinical use of these agents in severe asthma without ABPA is not currently recommended. Further research is needed to better delineate the potential utility of antifungal medications in severe asthma and identify the asthma populations who benefit from such treatment.